(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Today, together with the positive features of the globalization process, there are also negative features, that nationalism is becoming clearer day by day, and the foundations of national education are being undermined. This, in turn, puts mankind in front of the tasks that cannot be postponed in the matter of education. It is an important and urgent task to ensure that the growing young generation is responsible for the issue of family and marriage, which is considered the main link and support of society, and to educate them on the basis of national education.